Exploring the Charge Transport in Conjugated Polymers. Issue 41 (28th August 2017) - Xu, Yong; Sun, Huabin; Li, Wenwu; Lin, Yen‐Fu; Balestra, Francis; Ghibaudo, Gerard; Noh, Yong‐Young
Abstract: Conjugated polymers came to an unprecedented epoch that the charge transport is limited only by small disorder within aggregated domains. Accurate evaluation of transport performance is thus vital to optimizing further molecule design. Yet, the routine method by means of the conventional field‐effect transistors may not satisfy such a requirement. Here, it is shown that the extrinsic effects of Schottky barrier, access transport through semiconductor bulk, and concurrent ambipolar conduction seriously influence transport analysis. The planar transistors incorporating ohmic contacts free of access and ambipolar conduction afford an ideal access to charge transport. It is found, however, that only the planar transistors operating in low‐field regime are reliable to explore the inherent transport properties due to the energetic disorder lowering by the lateral field induced by high drain voltage. This work opens up a robust approach to comprehend the delicate charge transport in conjugated polymers so as to develop high‐performance semiconducting polymers for promising plastic electronics. Abstract : Conventional and planar polymer transistors are compared to explore the charge transport in conjugated polymers. The former is found to suffer from extrinsic effects of Schottky barrier, access transport, and ambipolar conduction. The latter is free from such issues so is more reliable for transport exploration. However, only those operating in the low‐field regime are reliable to explore the charge transport.